ИЗУЧЕНИЕ ЗНАЧЕНИЯ ВО ВРЕМЕНИ В ЯЗЫКАХ РАЗЛИЧНЫХ СИСТЕМ - Хошанов, Б.Х. (SCIENCE and SOCIETY, 2016)
The article is devoted to the study of value of limitation in time in the languages of different systems. The methods of transmission of value of limitation in time are examined by the constructions with a preposition «to» and their equivalents in the Karakalpak language.
Keywords: case; preposition; time; word combination; direction; object; verbs of motion; sentence; equivalent; limitation; construction; prefix